Exploring language variation, diversity and change - Burada, Marinela; Tatu, Oana; Sinu, Raluca (Cambridge Scholars Publishing, 2021)
While communication is becoming increasingly multimodal, verbal language and its use in different communicative situations still hold centre-stage in many research circles. The articles in this book explore native and second languages from three vantage points: syntactic structure, their uses in professional settings, and second/foreign language pedagogy. Using different methods and methodologies, the contributions here draw on both theoretical and empirical data in order to investigate a series of language-internal and language-external factors that both account for the structural peculiariti.